Effects of Viscous Dissipation and Radiation on Magnetohydrodynamic Free Convection flow along a Sphere with Joule Heating and Heat Generation - Miraj, M.; Alim, M. A.; Andallah, L. S. (Science & Technology Asia, 2015)
The effects of viscous dissipation and radiation on magnetohydrodynamic(MHD) free convection flow along a sphere with joule heating and heat generation have been investigated. The governing equations are transformed into dimensionless non-similar equations by using set of suitable transformations and solved numerically by the finite difference method along with Newton’s linearization approximation. We have focused our attention on the evaluation of velocity profiles, temperature profiles, shear stress in terms of local skin friction and the rate of heat transfer in terms of local Nusselt number for different values of radiation parameter, Prandlt number, heat generation parameter, magnetic parameter, joule heating parameter and viscous dissipation parameter and the numerical results have been shown graphically. Keywords: Natural convection, Radiation, Prandtl number, Heat generation, Nusselt number, Joule heating parameter, Viscous dissipation parameter and Magnetohydrodynamic.